2017
DOI: 10.1530/jme-17-0124
|View full text |Cite
|
Sign up to set email alerts
|

miR-212 mediates counter-regulation on CRH expression and HPA axis activity in male mice

Abstract: The mechanisms of hypothalamic-pituitary-adrenal (HPA) axis regulation have been studied persistently but still are not elucidated. Considering the emerging roles of microRNA in stress response, we conducted a microRNA microarray in mice hypothalamus to identify the potential role of microRNAs in regulating the HPA axis. In total, 41 microRNAs changed during heat stress in which we found that miR-212 contains a binding sequence with corticotropin-releasing hormone () 3'UTR according to a sequence analysis. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 61 publications
2
12
0
Order By: Relevance
“…However, TCRβ−/−δ−/ − and WT mice showed similar stress reactivity as shown by similar peripheral corticosterone responses to RRS. This finding is concordant with the mirrored increases in plasma CORT found in both RAG-1−/− and WT C57Bl/6 mice exposed daily to RRS and cage-switch stress in addition with a host of previous literature that has demonstrated that RRS is associated with a robust elevation of serum of plasma CORT in mice (Klenerova et al, 2018;Marvar et al, 2012;Tang et al, 2017;Kim and Han, 2009).…”
Section: Discussionsupporting
confidence: 88%
“…However, TCRβ−/−δ−/ − and WT mice showed similar stress reactivity as shown by similar peripheral corticosterone responses to RRS. This finding is concordant with the mirrored increases in plasma CORT found in both RAG-1−/− and WT C57Bl/6 mice exposed daily to RRS and cage-switch stress in addition with a host of previous literature that has demonstrated that RRS is associated with a robust elevation of serum of plasma CORT in mice (Klenerova et al, 2018;Marvar et al, 2012;Tang et al, 2017;Kim and Han, 2009).…”
Section: Discussionsupporting
confidence: 88%
“…This may because that there is no change in the gene expression of POMC in the pituitary, which also occurred in heat stress experiments in rats (50). Additionally, it is indicated that heat stress regulates CRH expression and HPA axis activity by affecting miR-212 (23). In our study, we found that miR-130a-3p inhibited PRL expression.…”
Section: Discussionsupporting
confidence: 53%
“…Besides, in our work-in-progress research focused on the genome wide analysis of non-coding RNA in pituitaries of normal and heat-stressed sows, heat stress has already been found to affect miR-130a-3p expression as well as PRL expression. Moreover, studies have shown that miRNAs participate in heat stress response (23), and heat stress induces alteration of endocrine hormones (24). Taken together, data above may suggest a potential relationship among miR-130a-3p, PRL and heat stress.…”
Section: Introductionmentioning
confidence: 68%
“…Then, 40 μg of protein was mixed in a buffer (25% glycerol, 2% SDS, 0.01% bromophenol blue, Tris–HCl, pH 6.8) and heated at 100°C for 5 min. The samples were subjected to 10% SDS-PAGE, followed by transfer onto a PVDF membrane (Roche) using the GelDoc XR system (Bio-Rad) ( Tang et al 2017 ). The membrane was washed with Tris-buffered 154 mmol/L NaCl solution with 0.1% Tween 20, and incubated with anti-rabbit neuritin (Abcam, Catalog #64186), GFAP (Abcam, Catalog #ab7260), JAK2 (Abcam, Catalog # ab108596), p-JAK2 (Abcam, Catalog #ab32101), STAT3 (Abcam, Catalog #ab68153), p-STAT3 (Abcam, Catalog #ab76315), or β-actin polyclonal antibody (100 in dilution, Sigma, Catalog #A2103) for 1 h at 25°C, and incubated with peroxidase-conjugated anti-rabbit IgG (1:1000) for 1 h at 25°C.…”
Section: Methodsmentioning
confidence: 99%